Surface Mineralization of the TiO2-SiO2/PES Composite Membrane with Outstanding Separation Property via Facile Vapor-Ventilated In Situ Chemical Deposition - Gan, Ning (Langmuir : the ACS journal of surfaces and colloids, 2022)
Conventional polymeric membranes are broadly employed in water treatment processes; however, most of them suffer from relatively low water permeance and severe membrane fouling phenomena owing to their relatively hydrophobic nature. In this work, a novel class of inorganic-organic composite membranes was developed through a newly developed vapor-ventilated in situ chemical deposition method, where the Ti and Si precursors were first hydrolyzed and then conferred into metal oxides to form a continuous TiO2-SiO2 modification layer. Owing to the distinct physicochemical properties, the Ti and Si precursors were leveraged as quasi-molecular regulators to tune the membrane surface chemistry and pore aperture (within the nanoscale) to benefit highly efficient water purification by underpinning the rapid transport of water molecules and featuring an excellent fouling-resistant and fouling-releasing property against typical pollutants. The as-developed TiO2-SiO2/PES composite membrane showed a high water permeance of 187.4 L·m-2·h-1·bar-1, together with a relatively small mean pore aperture of 4.2 nm, showing an outstanding permeating efficiency among state-of-the-art membranes with a similar separation accuracy. This study provides a paradigm shift in membrane materials that could open avenues for developing high-performance inorganic-organic composite membranes for complex wastewater treatment